PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (Kajian Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2015-2019) - Annisa Devi Lestari; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2021)
This research aimed to determine the influence of corporate governance and corporate social responsibility on the value of companies in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. We used the purposive sampling method for collecting data. The data were manufacturing companies listed on the Indonesia stock exchange (IDX) and conducted the Corporate Social Responsibility. The final samples of this study are 46 companies with 205 annual reports that meet sample selection criteria from 2015 to 2019.Data were analyzed using multiple regressions. Good corporate governance was proxied by the number of commissioners, institutional ownership, managerial ownership, audit committee, and the independent board of commissioners. The results showed that the number of commissioners, institutional ownership, managerial ownership, audit committee, and Corporate Social Responsibility (CSR) had a positive and significant influence on the firm value. In contrast, the independent board of commissioners has no considerable effect.